KUALITAS PELAYANAN PUBLIK DI ERA DIGITALISASI KANTOR KECAMATAN DUAPITUE KABUPATEN SIDENRENG RAPPANG - Mappagiling, Muh Ihsan; Usman, Jaelan; Syukri, Syukri (Universitas Muhammadiyah Makassar, 2024)
This research aims to find out about the quality of public services in the era of digitalization at the Duapitue District Office, Sidenreng Rappang Regency. This type of research uses qualitative research with a descriptive type that focuses on the quality of public services in the era of digitalization at the Duapitue District Office, Sidenreng Rappang Regency. The results of this research indicate that the existence of Transparency in Dua Pitue District regarding openness in the public service process is not good enough. This is characterized by openness regarding service procedures, not yet well publicized and not yet understood by some people. Accountability at the Dua Pitue District Office. The sub-district government carries out its duties and functions properly and correctly based on standard service procedures. Participation in the Dua Pitue District Office is the provision of services (serving) the needs or people who have an interest in the organization in accordance with the basic rules and mental involvement of a person in achieving goals, as well as taking responsibility for it. equality of rights and human resources must have extensive scientific capabilities in providing services and speed in providing information as well as accuracy, friendliness and comfort.